UBVRI POLARIMETRY OF CLOSE BINARY SYSTEM V448 Cyg - N. M. Shakhovskoy; G. V. Volkova; Yu. L. Manilov; N. H. Minikulov (Odessa Astronomical Publications, 2017)
ABSTRACT. Analysis of the polarimetric measurements of the eclipsing binary system V448 Cyg in wide UBVRI niters has shown the presence of the following components of the polarization: a) interstellar; b) constant intrinsic polarization with a flat spectrum; c) phase-dependent contribution, the amplitude of which decreases with wavelength. Constant component is possibly caused by an extended disk-like optically thin refracting envelope; the variable one may be caused by relatively dense condensations near the Lagrangian points in a binary. By analyzing the Fourier harmonics, the inclination angle is found to be i = 82°. The orbital plane of the system is inclined in respect to the Galaxy plane at an angle 70°. Mass of the extended envelope is estimated to be 1.5 x 10-8 M☉ with a mass loss rate 8.6 x 10-7 M☉/yr. Key words: Stars: binaries: close, eclipsing; circumstellar matter; polarization.